(untitled) (Research, Society and Development, 2022)
The Metabolic Syndrome (MS) represents a condition of pro-thrombotic and pro-inflammatory state characterized by increased inflammatory activity of cytokines. Dysbiosis processes have been associated with obesity, present in MS, so the use of probiotics has been considered as an alternative to traditional approaches to weight loss and a low-calorie diet, provided they are consumed in adequate amounts. This is an integrative literature review, whose guiding question “Does the use of probiotics reduce the inflammation generated by the metabolic syndrome?” induced the research carried out in the databases: SCIELO, VHL, PUBMED and Science Direct. The descriptors “inflammation”, “probiotic”, “metabolic syndrome” and “insulin resistance” were used. The articles were analyzed using the PRISMA model, and 8 articles were included in the final sample for review. All included studies were published in the year 2017 to 2022 in English. The probiotic effect on body weight is dependent on a number of factors, such as the species and strains of microorganisms and the time of administration of the probiotic. Some of them have been widely used in patients with MS to reduce the inflammatory state of the body, acting mainly in reducing body weight, BMI, waist and hip circumferences, systolic and diastolic blood pressure. In addition, there was a reduction in pro-inflammatory markers such as interleukin 5 and C-reactive protein with the use of probiotics. These findings justify the need for multicentric research, with a heterogeneous population to be analyzed in order to accurately determine the therapeutic effects of probiotics in reducing inflammatory markers and cardiometabolic risk factors in patients with MS.